FinTechs, BigTechs and banks: When cooperation and when competition? - Janina Harasim (Journal of Risk and Financial Management, 2021)
While there is a fast-growing number of studies on FinTech, the relationships between technology companies and banks have received only limited attention in the research literature. Most of the studies on FinTech-bank interactions conducted so far address the questions: why banks collaborate with FinTechs (reasons) and how they do it (forms of cooperation), whereas this paper aims at clarifying when the most likely form of their interaction is cooperation and when competition. To cover this cognitive gap, the conceptual framework to help explain which factors affect the type of interactions between technology companies and banks is presented in this paper. Based on extensive literature review and using the market-based approach, the external factors of the market position of banks and technology companies were examined. It was found that this position and therefore the basic type of interaction depends on the adoption level of FinTechs and BigTechs in individual countries/regions. The adoption of FinTechs and BigTechs turned out to be higher in EMDEs and lower in AEs, which makes it more likely that in the first group of countries tech companies would tend to serve as banks' competitors, whereas in the second group they would rather collaborate with banks or choose the coopetition strategy. When analyzing internal factors, the resource-based approach and a slightly modified IO theory were applied. In this part, the strategic tool which enables the assessment of the extent to which assets, skills, and features of FinTechs, BigTechs and banks are complementary (which gives the rationale for cooperation) or substitutable (which gives the rationale for competition) was proposed. This study is a critical analysis based on desk research, that contributes to the existing literature by (1) providing a narrow definition of FinTech representing the subjective/institutional approach, (2) considering separately FinTechs and BigTechs, and (3) proposing the strategic tool which helps to assess comparative advantages of banks, FinTechs and BigTechs, and thus makes it easier to choose the most appropriate type of their interaction.
Keywords: 330; FinTech; BigTech; banks; competition; cooperation; coopetition